In-situ non-destructive monitoring of water flow in damaged agricultural pipeline by AE - Suzuki, Tetsuya, author; Ohtsu, Masayasu, author; Aoki, Masao, author; Nakamura, Riota, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Deterioration of water-flow function in a pipeline system has resulted from water-leak accidents due to damage accumulation in pipe materials. The repaired pipeline system cannot be evaluated of water-leak phenomena under the inner water pressure condition. Non destructive evaluation of water-flow function in pipeline system is currently in urgent demand. In this study, acoustic emission (AE) method is applied to the evaluation of water-flow function in an existing agricultural pipeline, which was inspected and then repaired after water-leak accidents. At three conditions, experiments were conducted. First, a water leak phenomenon which the pipeline filled full with water was investigated. Secondly, an evaluation process of water-drained from full to empty condition was made in the pipeline. Thirdly, experiments were carried out condition of the pipeline was filled with water after repairing the water-leak section. AE method was applied to detecting signals of water-leak and flow under these conditions. The results show that water-leak in the pipeline system could be quantitatively evaluated by using such AE parameters, such as generation behavior and AE energy. In the third condition, AE generation behavior was varied with the situation of the pipeline until the pipeline was filled with water. AE energy showed the same tendency as AE generation behavior. When an AE sensor was installed on an air valve, AE energy dropped temporarily as the pipeline was being filled with water. However, when water was filled up to the air valve, the increase in AE energy was confirmed. Thus, it becomes clear that when a pipeline is being filled with water after the repair, the situation of water in the pipeline can be clearly identified through AE monitoring. Discharge evaluation of a damaged pipeline system can be conducted in a short time through AE monitoring.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.